Pengelolaan Pembelajran Anak Berkebutuhan Khusus pada Kelas Inklusi - Khurotul Uyun; Romi Dewi Astuti; Tri Widya Ningsih; Karfica Nofridayana; Hendri Marhadi (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
Management of learning for children with special needs is carried out to ensure that all students receive appropriate and quality education so that they can develop optimally according to their potential. This research aims to describe the learning management carried out in inclusion classes. The design used in this research is a literature study. The research results show that learning management uses an individualization approach, a collaborative approach, behavior modification, use of media and the provision of friendly learning, as well as collaboration teacher and parent. Conclusions from this research: Teachers in inclusion classes need to adapt learning management to the needs, abilities and characteristics of students who have special needs.